PROGRAM PELAYANAN SEKOLAH UNTUK MENGEMBANGKAN ENTERPRENEUR MUDA PADA SMA KRISTOFORUS II - Toar, Yandri Ardolof Bowo Laksono (LP2M STP Mataram, 2024)
In the era of globalization and rapid technological advancement, entrepreneurial skills have become essential competencies for the younger generation. Formal education often emphasizes academic aspects without adequately developing practical skills relevant to the real world. Therefore, the role of schools in fostering an entrepreneurial mindset is crucial. The Young Entrepreneurs School Service Program is designed to teach important entrepreneurial skills through interactive, project-based learning. This program includes identifying business opportunities, designing small enterprises, and implementing business plans in schools and communities. Collaboration with local entrepreneurs and professional mentors supports a holistic learning ecosystem. The training methods include motivational sessions, workshops, business plan development, and marketing simulations, concluding with evaluations. The results of the training at SMA Kristoforus II demonstrated high enthusiasm from students and an increase in entrepreneurial skills. Through this approach, students are expected not only to understand entrepreneurial concepts theoretically but also to gain comprehensive practical experience. The program aims to create an independent, creative young generation prepared to face future economic challenges and potentially become agents of change capable of driving local and national economic growth